Timelines of everyone : from Cleopatra and Confucius to Mozart and Malala / senior editor: Steven Carton ; illustrators: Peter Bull [ja kymmenen muuta] - Carton, Steven; Bull, Peter (DK, 2020)
Get the inside track on the incredible lives of history's must-know names: from Shakespeare to Oprah Winfrey, and Anne Frank to Julius Caesar. This book boasts more than 150 visual timelines, covering a diverse array of kings and queens, humanitarians, scientists, inventors, explorers, activists, writers, artists, and more, from all over the globe. It breathes fresh life into the biographies of the people you thought you knew, and unearths many stories from previously ignored or unheard voices.
Keywords: merkkihenkilöt; henkilöhistoria; maailmanhistoria; historia; kronologia